Emerging Data from a Newborn Hearing Screening Program in Sharjah, United Arab Emirates - Muhammed Ayas; Hakam Yaseen (Hindawi Limited, 2021)
Objectives. Newborn hearing screening (NHS) plays a critical role in early identification of hearing loss and subsequent early habilitation. Active parental involvement influences the success of NHS, particularly the initial NHS and follow-up. The current study reports the results of an NHS program in a cohort of babies born in a tertiary care hospital in Sharjah, United Arab Emirates (UAE). Further, it explores a two-stage NHS model to reduce false responses, thereby alleviating parental anxiety. Methods. Retrospective observational study was conducted for a period of five years from January 2017 to December 2020. NHS was done as a two-stage model. All the healthy newborn babies were screened using Automated Auditory Brainstem Response (AABR) by trained audiology professionals. Babies who failed the first NHS were followed up after two weeks. Further, babies that failed the follow-up NHS were sent for diagnostic hearing evaluation and intervention as necessary. Results. A total of 1821 newborn babies were screened during the study period. Eighty-one percent of babies passed the initial NHS. Four hundred and twenty-three (23.22%) babies were referred on the first NHS and were followed up after 2 weeks. Among these babies, 7.03% (24) failed second NHS. Nine (37.50%) of the 24 babies were confirmed to have hearing loss in both ears. The incidence of hearing loss in our cohort was 4.94 per 1000. Confirmed hearing loss was statistically higher in boys than girls (p<0.05) Conclusion. Current study was an attempt to report the emerging NHS data as part of the implementation of an NHS program. The study findings emphasize the need for a two-stage model of NHS to rule out false responses.